2013
DOI: 10.4236/abb.2013.42030
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulolytic activities of a novel strain of <i>Trichoderma harzianum</i>

Abstract: This study describes a novel dark-green spore producing strain of Trichoderma harzianum exhibiting higher activities of cellulase, hemicellulase and ligninase on specific plate assays. To assess the cellulase production in detail, basal salt medium (BSM) was supplemented with synthetic [carboxymethyl cellulose (CMC), glucose, sucrose, dextrose, lactose or maltose] and natural (flours of banana, banana peel, jack seed, potato or tapioca) carbon as well as nitrogen (yeast extract, beef extract, peptone, NaNO 3 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
(26 reference statements)
3
12
0
Order By: Relevance
“…Maximum enzyme production was achieved with NaNO 3 as best nitrogen source. Similar findings were also reported by Rubeena et al [14]. Akinola et al [11] reported casein as a best nitrogen source for endoglucanase production by T. harzianum in submerged fermentation.…”
Section: Effect Of Sugarssupporting
confidence: 89%
“…Maximum enzyme production was achieved with NaNO 3 as best nitrogen source. Similar findings were also reported by Rubeena et al [14]. Akinola et al [11] reported casein as a best nitrogen source for endoglucanase production by T. harzianum in submerged fermentation.…”
Section: Effect Of Sugarssupporting
confidence: 89%
“…Table 2 shows that T. harzianum is more effective to increase crude protein content and decrease crude fibre in substrat contained high fibre such as pineapple peel than that of low fibre such as banana peel. It is in agreement with Rubeena et al, (2013) who stated that T. harzianum was potential to hydrolize biomass due to its elevated cellulose production and cellulolytic activity. DelgadoJarana et al, (2002) stated that T. harzianum has protease activity and was not responsible on glucanase degradation.…”
Section: Resultssupporting
confidence: 92%
“…Fungus MT23 produced yellow pigment started at the fourth day of cultivation and ready to be harvested on day fourteenth. Pradeep and Pradeep (2013) studied the optimum cultivation condition for pigment production of fungus Fusarium moniliforme. The fungus had highest pigment absorbance (AU 500nm) at temperature 28-30 o C, pH 5.5, glucose as carbon source, peptone as nitrogen source and cultivated for 8 days.…”
Section: Pigment Extractionmentioning
confidence: 99%
“…Environmental conditions have important role in fungi growth. Pradeep and Pradeep (2013) studied the optimum cultivation condition for growth of fungus Fusarium moniliforme. The fungus had highest biomass (g/L) at temperature 28 o C, pH 5.5, glucose as carbon source, peptone as nitrogen source, KH 2 PO 4 as source of salt and addition of methionine as additional amino acid.…”
Section: Pigment Extractionmentioning
confidence: 99%
See 1 more Smart Citation